Evaluation of Tax Policy on Interest and Dividend of IPO - Nurchamid, Tafsir (UI Scholars Hub, 2013)
This research papers on the evaluation of tax policy interest loan and dividend of the company listed in the Indonesia Stock Exchange consists of five sections. (1). Introduction that describes the problem of conceptual and factual studies that led to the research problems were raised by writer. (2). Literature review presents several theories and key concepts which are used to obtain a theoretical answers and basic understandings to the problem of research. (3). Research method is operationalization of the steps to answer the research problem, data collection and data analyzing. (4). Research finding and discussion of research finding based on research problem rising. (5). Conclusions and suggestions may be given to related parties.